Galermi au fil de son eau : un aqueduc syracusain dans la reconfiguration de son territoire - Sophie Bouffier; Fabienne Wateau (Développement Durable et Territoires)
How can we write the history of the Galermi aqueduct (Syracuse, Italy) from ancient times to the present day? This paper intends to report the first results of an interdisciplinary collective research program by emphasizing the different periods of the Galermi water: the aim is to identify the challenges and the so-called hydrosocial relations of this object from its technical, social and political history. What technical readings and representations of the hydraulic structure could be proposed over the ages? What control did this technical work undergo? By whom? Why? What social dynamics and actors can be identified and analyzed? What future and possible conservation can be suggested and set up for the sustainability of a monument that dates back more than 2,000 years? From Greeks and Romans to today’s policymakers, between influence and power, planning of land and Heritage, the reader is encouraged to discover this long underground aqueduct whose uses and purposes have been adapted through the ages: potable-water supply of the ancient and modern town of Syracuse, hydraulic energy for water mills during the 16th-19th centuries, hydraulic power station in the 20th century, irrigation since the 19th century.